Fire-safe and environmentally friendly nanocomposites based on layered double hydroxides and ethylene propylene diene elastomer. Issue 31 (11th March 2016) - Basu, Debdipta; Das, Amit; Wang, De-Yi; George, Jinu Jacob; Stöckelhuber, Klaus Werner; Boldt, Regine; Leuteritz, Andreas; Heinrich, Gert
Abstract : The capability of layered double hydroxide has been explored as a potential flame retardant filler and the effect of the mechanical properties, dynamic mechanical properties, and thermal stability of the composites was also studied. Abstract : In this work we describe layered double hydroxide (LDH), known as naturally occurring hydrotalcite, based rubber composites that can serve as outstanding fire retardant elastomeric materials. The preparation and detailed characterization of these composites are presented in this study. The inherent slow sulfur cure nature of EPDM rubber is considerably improved by the addition of LDH as realised by the observation of a shortening of the vulcanization time and an improvement of ultimate rheometric torque. This behavior of LDH signifies not only the filler-like character of itself, but also offers vulcanization active surface properties of layered double hydroxide particles. A good rubber–filler interaction was also realised by observing a positive shift of the glass transition temperature of ethylene propylene diene rubber (EPDM) in dynamic mechanical analysis (DMA). The flame retardant property was studied by the cone calorimeter test. The cone calorimeter investigation with sulfur cured gum rubber compounds found a peak heat release rate (PHRR) value of 654 kW m −2 . However, at a higher phr loading of Zn–Al LDH i.e., at 40 phr and 100 phr, the PHRR is diminished to 311 kW m −2 and 161 kW m −2, respectively. Thus, this present work can pave the way to fabricate environmentally friendly fire retardant elastomeric composites for various applications.